Moderating role of resilience on professional quality of life, stress and turnover intention among oncology nurses - Asma Al Yahyaei; Zainab Al Kindi; Sulaiman Al Sabei; Nabiha Al Hasni; Wafa Al Jabri; Joshua Muliira (BMC Nursing)
Abstract Background Oncology nurses often face high levels of stress and emotional demands due to the nature of their work with vulnerable patients and families. These challenges can influence their professional quality of life (ProQOL) and intentions to leave the profession. This study explored whether resilience moderates the relationship between ProQOL, including compassion satisfaction, burnout, and secondary traumatic stress, and turnover intention among oncology nurses in Oman. Methods A descriptive cross-sectional study was conducted using convenience sampling with 456 nurses from two national cancer centers in Oman. Data were collected using a self-administered questionnaire that included the ProQOL Scale, Connor-Davidson Resilience Scale, Brief Nursing Stress Scale, and Turnover Intention Scale. Descriptive statistics summarized the data, and regression analysis was used to examine associations and predictive relationships. Results Participants reported high compassion satisfaction (mean = 43.16 ± 5.56), moderate burnout (mean = 25 ± 4.96), and low to moderate secondary traumatic stress (mean = 24.13 ± 8.26). Resilience levels were moderate (mean = 27.18 ± 6.99), as were stress (mean = 1.53 ± 0.59) and turnover intention (mean = 2.45 ± 0.87). Turnover intention was negatively correlated with compassion satisfaction (r = -.31, p < .01) and resilience (r = -.31, p < .01), and positively correlated with burnout (r = .23, p < .01) and secondary traumatic stress (r = .30, p < .01). While resilience was associated with turnover intention, it did not moderate the relationship between professional quality of life and turnover intention. Key predictors of turnover intention included compassion satisfaction, resilience, burnout, secondary traumatic stress, expatriate status, and educational level. Conclusions Turnover intention among oncology nurses in Oman is influenced by both individual traits and job-related factors. While resilience plays a role, modifiable factors such as compassion satisfaction, burnout, and secondary traumatic stress are significant predictors. Addressing these modifiable factors through targeted interventions that enhance compassion satisfaction and reduce burnout, and secondary traumatic stress may help lower turnover intention, strengthen the oncology nursing workforce, and improve the continuity and quality of cancer care.